2007
DOI: 10.1111/j.1748-7692.2007.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Killer Whale Predation on Steller Sea Lions From Field Observations in Kenai Fjords, Alaska

Abstract: The behavioral and predatory patterns of Gulf of Alaska (GOA) transient killer whales (Orcinus orca) were studied between 2000 and 2005 using remote video and vessel‐based observations near the Chiswell Island Steller sea lion (Eumetopias jubatus) rookery and in the broader Kenai Fjords (KF) region of the northern GOA. GOA transient killer whales were observed on 118 d over the 6‐yr period; the median group size was two (range: 1–9). Nine predation events were observed from vessels and an additional sixteen we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…Given trends observed in most of the Aleutian Islands (which include 2 of the 6 Alaska regions), it is unclear whether the western stock will meet the second criterion by 2015. Research will continue on understanding the possible causes of the continued decline west of Samalga Pass, which include nutritional stress re lated to environmental change or fisheries (NRC 1996, NMFS 2000, 2010, Malavear 2002, Trites & Donnelly 2003, Fritz & Hinckley 2005, Trites et al 2007, Atkinson et al 2008, predation by killer whales (Springer et al 2003, Williams et al 2004, Maniscalco et al 2007, Horning & Mellish 2012, contaminants and disease that could impair reproduction (Burek et al 2003, Atkinson et al 2008, Castellini et al 2012, and incidental and intentional takes in Russian fisheries (Burkanov et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Given trends observed in most of the Aleutian Islands (which include 2 of the 6 Alaska regions), it is unclear whether the western stock will meet the second criterion by 2015. Research will continue on understanding the possible causes of the continued decline west of Samalga Pass, which include nutritional stress re lated to environmental change or fisheries (NRC 1996, NMFS 2000, 2010, Malavear 2002, Trites & Donnelly 2003, Fritz & Hinckley 2005, Trites et al 2007, Atkinson et al 2008, predation by killer whales (Springer et al 2003, Williams et al 2004, Maniscalco et al 2007, Horning & Mellish 2012, contaminants and disease that could impair reproduction (Burek et al 2003, Atkinson et al 2008, Castellini et al 2012, and incidental and intentional takes in Russian fisheries (Burkanov et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Optimal foraging theory predicts individual variability in prey selection, a prediction largely supported by empirical data. Populations of predators in the wild indeed rarely consist of individuals with consistent, identical preferences for particular types of prey, and phenotypic attributes of predators such as age (Rutz et al 2006;Field et al 2007), sex (Cooper et al 2007), reproductive status (Pierce et al 2000), group size (Packer et al 1990), family structure (Gaydos et al 2005;Maniscalco et al 2007) or social status (Saulitis et al 2000) are all factors that can affect a predator's diet (Table 2). Female mountain lions with offspring, for example, preferentially select female deer, while males and females without offspring do not (Pierce et al 2000).…”
Section: Individual Variability In Prey Selection Predator Efficiencmentioning
confidence: 98%
“…Direct observations (Ford et al, 1998;Maniscalco et al, 2007), physical evidence (Heise et al, 2003), and telemetered data Mellish, 2009, 2012) reveal the occurrence of predation on Steller sea lions. From a review of research conducted through the 1990s, the National Research Council (2003) concluded that the recovery of the WDPS was more likely limited by predation than by resource-driven effects.…”
mentioning
confidence: 99%